Adapting Food Industry Supply Chains to Growing Challenges of Fruit Procurement in a Changing Climate - Florian, Pollet (2025)
While the impacts of climate change on agriculture and the solutions to overcome them are well-documented, the consequences for the agri-food industry sector remain underexplored. This thesis investigates how French Small and Medium-sized Enterprises (SMEs) in the fruit-based sector (producers of jam, juice, yogurt, etc.) are adapting their value chains to the escalating supply disruptions due to the impacts of climate change on fruit production. Drawing on a theoretical framework of climate risk and supply chain resilience, this research utilizes a qualitative methodology comprising a literature review and two rounds of thirteen semi-structured interviews with industry professionals. The findings reveal a critical paradox: while SMEs possess a strong awareness of climate risks, their responses remain predominantly reactive rather than strategic. The study identifies that companies largely rely on incremental adaptation measures, such as geographic diversification of suppliers, extended storage of raw materials (to generate buffer stocks), and recipe reformulation, rather than transformational structural changes. Crucially, the research highlights a tension between supply security and market positioning: as domestic and organic harvests become volatile, SMEs are forced to balance the commercial imperative of "French Origin", “natural” and organic branding with the logistical necessity of importing raw materials or replacing them with aromas. The thesis concludes that to ensure long-term viability, the sector must transition from ad-hoc crisis management to anticipatory, transformational adaptation strategies that integrate climate foresight into the core business model.